2009
DOI: 10.1126/science.1178583
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing the 3D Internal Structure of Calcite Single Crystals Grown in Agarose Hydrogels

Abstract: Single crystals are usually faceted solids with homogeneous chemical compositions. Biogenic and synthetic calcite single crystals, however, have been found to incorporate macromolecules, spurring investigations of how large molecules are distributed within the crystals without substantially disrupting the crystalline lattice. Here, electron tomography reveals how random, three-dimensional networks of agarose nanofibers are incorporated into single crystals of synthetic calcite by allowing both high- and low-en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
287
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 266 publications
(303 citation statements)
references
References 31 publications
15
287
0
1
Order By: Relevance
“…Bottom-up self-assembly can generate diverse patterns through a much more complex evolution of forces than we could ever apply by hand (12), but ceding control over all but the starting materials leaves little opportunity to fine-tune structures or control stages of hierarchical development, let alone rationally design arbitrary architectures. Strategies inspired by biomineralization have been explored as potential routes to controlling growth and self-assembly from the molecular level via tailored microenvironments, epitaxy and inorganic or organic additives (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Yet although these have produced some interesting spherical, spiral, leaf-like, and other shapes (25)(26)(27)(28)(29)(30)(31)(32), it is rather disappointing that the appearance of various forms in synthetic systems is often unexpected and the attempts to identify the mechanisms of their formation are generally assessed a posteriori..…”
mentioning
confidence: 99%
“…Bottom-up self-assembly can generate diverse patterns through a much more complex evolution of forces than we could ever apply by hand (12), but ceding control over all but the starting materials leaves little opportunity to fine-tune structures or control stages of hierarchical development, let alone rationally design arbitrary architectures. Strategies inspired by biomineralization have been explored as potential routes to controlling growth and self-assembly from the molecular level via tailored microenvironments, epitaxy and inorganic or organic additives (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Yet although these have produced some interesting spherical, spiral, leaf-like, and other shapes (25)(26)(27)(28)(29)(30)(31)(32), it is rather disappointing that the appearance of various forms in synthetic systems is often unexpected and the attempts to identify the mechanisms of their formation are generally assessed a posteriori..…”
mentioning
confidence: 99%
“…4e) indicates that the cuprite crystal is able to grow around the particles without significant disruption to its lattice, in agreement with similar reports for particle and fiber encapsulation within calcite. 36,38 Optoelectronic heterostructures, and to potentially become more complex, resulting in splitting of the single plasmon peak into low and high energy coupled (hybridized) modes. 72,73 As compared to discrete core-shell architectures, the Au nps in our rods have varying lengths of contact between them.…”
Section: Encapsulation Of Particles In Single Crystals the Confinemementioning
confidence: 99%
“…With the incorporation of guest materials such as bio-micromolecules [1,2], cellular tissue networks [3], and organic molecules into the inorganic matrix [4][5][6][7], the biominerals generated often show enhanced mechanical and optical properties. Examples include sea urchin skeletons, mollusk shells, teeth, and bones, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Using annular dark-field scanning TEM, they were able to visualize the 3D structure of hydrogel networks inside the single crystals. They concluded that the incorporation of the uncharged agarose hydrogel networks into the calcium carbonate single crystal structure was a simple physical entrapment process rather than a chemical process, due to the lack of specific crystal face of calcium carbonate that was associated with chemical process [7]. Recently De Yoreo et al used in-situ liquid-phase transmission electron microscopy (TEM) technique to study the nucleation of calcium carbonate in the matrix of polystyrene sulphonate and revealed that such process is driven by specific ionbinding and is independent of any other factors that contributed to the free-energy barriers [23].…”
Section: Introductionmentioning
confidence: 99%